Unsur “Penasaran: Menarik dan Menggelitik” dalam “Permainan Bahasa” pada Teks Promosi Pariwisata - Ary Setyadi (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2022)
AbstractThe main and especially function of language, including Indonesian, is a communication tool, both in the form of spoken and written variety. The content of the message can be packaged in a straightforward manner/denotation or figure of speech/connotation. The existence of Indonesian as a tourism promotion tool, because tourism objects are not always packaged in a straightforward manner, but can be packaged in a figurative way (so that the form of